Cities, business, and the politics of urban violence in Latin America - Moncada, Eduardo (Stanford University Press, 2016)
Cities, Business, and the Politics of Urban Violence in Latin America analyzes and explains the ways in which major developing world cities respond to the challenge of urban violence, introducing business as a pivotal actor in the political economy of urban violence.